2016
DOI: 10.1371/journal.pone.0160315
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Ligand Binding Sites on Protein Surfaces by 3-Dimensional Probability Density Distributions of Interacting Atoms

Abstract: Predicting ligand binding sites (LBSs) on protein structures, which are obtained either from experimental or computational methods, is a useful first step in functional annotation or structure-based drug design for the protein structures. In this work, the structure-based machine learning algorithm ISMBLab-LIG was developed to predict LBSs on protein surfaces with input attributes derived from the three-dimensional probability density maps of interacting atoms, which were reconstructed on the query protein sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…A simple solution to the Jmol issue is to use JSmol (10), a JavaScript replacement for Jmol. This is the avenue taken by 3DLigandSite (11), COFACTOR (12,13), COACH (14) ISMBLAB-LIG (15) and LIBRA (16). Though JSmol supports complex visualization options, it suffers from performance issues due to inefficiencies introduced when migrating Jmol code from Java to JavaScript.…”
Section: Introductionmentioning
confidence: 99%
“…A simple solution to the Jmol issue is to use JSmol (10), a JavaScript replacement for Jmol. This is the avenue taken by 3DLigandSite (11), COFACTOR (12,13), COACH (14) ISMBLAB-LIG (15) and LIBRA (16). Though JSmol supports complex visualization options, it suffers from performance issues due to inefficiencies introduced when migrating Jmol code from Java to JavaScript.…”
Section: Introductionmentioning
confidence: 99%
“…The general principles and technical details of the ISMBLab-PPI/PEP predictors have been published previously. 18,[24][25][26][27][28][29] Details of the computational methods are described in Supplementary Methods.…”
Section: Ismblab-ppi and Ismblab-pep Predictorsmentioning
confidence: 99%
“…The synthetic antibody scFv libraries were constructed with oligonucleotide-directed mutagenesis; [19][20][21][22][23][24] the enriched antigen-recognition determinants on the scFv variants were calculated with the ISMBLab package, which is a collection of machine learning predictors for quantitative antigen-recognition propensities on the antigen binding sites of the antibodies. 18,[24][25][26][27][28][29] The antigen-recognition propensity computation indicated that the scFv variants of the designed synthetic antibody libraries were encoded with multiple folds of CDR hot spot residues with high protein antigen recognition propensities compared with those of the human antibody germline sequences. Selected anti-protein antibodies from the synthetic antibody libraries were highly specific against the corresponding protein antigens with sub-nanomolar affinity without in vivo affinity maturation, indicating that the antibodies encoded with enhanced population of CDR hot spot residues could bind to protein antigens with high specificity and affinity, bypassing the in vivo affinity maturation processes involving somatic hyper mutations and clonal selections.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning has been also employed to solve partial tasks in complex eFindSite and COACH methods. Tools based primarily on machine learning have been introduced only very recently [ 32 , 33 ] (with notable earlier exception [ 34 ]). The latest one of them is DeepSite, a method based on multi-layer (for different atom types) voxelized representation of 3D space and deep convolutional neural networks.…”
Section: Introductionmentioning
confidence: 99%